Perlindungan hukum terhadap kreditur selaku pengambil alih kredit pada kreditur - Febry Firmansyah (University of Merdeka Malang, 2021)
Credit take over is a payment made by a third party to a creditor, who will replace his position as a new creditor to the debtor. The absence of standard rules regarding the implementation of credit take over has resulted in non-standardization of the credit take over implementation process. The purpose of this article is to examine the legal protection of the parties in implementing the take over at Bank Jatim Banyuwangi Branch. This type of research is empirical legal research where the study was conducted at Bank Jatim Banyuwangi Branch. The results of research conducted by a Notary/PPAT in Banyuwangi are included in the category of subrogation by way of law (Article 1403 of the Civil Code). In the implementation of take over credit protection is obtained through the re-signing of the SKMHT at the time of the Roya Letter, and a certificate of proof of ownership of the guarantee has been physically issued by the initial creditor. The implementation of the take over for new creditors at Bank Jatim Banyuwangi Branch is obtained through the re-signing of the SKMHT which is the basis for making APHT when the roya letter, proof of credit repayment, and certificate of proof of collateral ownership have been physically issued by the initial creditor (bank). The initial check before the certificate of proof of ownership is issued by the initial creditor is carried out by issuing a Land Registration Certificate (SKPT) through the BPN.How to cite item: Firmansyah, F. (2021). Perlindungan hukum terhadap kreditur selaku pengambil alih kredit pada kreditur. Jurnal Cakrawala Hukum, 12(2), 178-186. doi:https://doi.org/10.26905/idjch.v12i2.5812